Towards practical applications of quantum optics - Drahi, D (2019)
This DPhil thesis presents two key works towards practical applications of quantum optics. Both works are novel and achieve competitive state-of-the-art results. Today's most widely used method of encoding quantum information in optical qubits is the dual-rail basis, often carried out through the polarisation of a single photon. On the other hand, many stationary carriers of quantum information | such as atoms | couple to light via the single-rail encoding in which the qubit is encoded in the number of photons. As such, interconversion between the two encodings is paramount in order to achieve cohesive quantum networks. In the first part of this thesis, we demonstrate this by generating a hybrid entangled resource between the two encodings and using it to teleport a dual-rail qubit onto its singlerail counterpart. Our key results yield an average fidelity of F = (92:8±2:2)% for the teleportation and F = (89:7 ± 2:1)% for entanglement swapping, thus confirming the applicability of this scheme towards a real-world implementation. This work completes the set of tools necessary for the interconversion between the three primary encodings of a qubit in the optical field: single-rail, dual-rail and continuous-variable. A remarkable aspect of quantum theory is that certain measurement outcomes are entirely unpredictable to all possible observers. Such quantum events can be harnessed to generate numbers whose randomness is asserted based upon the underlying physical processes. In the second part of this thesis, we formally introduce and experimentally demonstrate an ultrafast optical quantum randomness generator that uses a totally untrusted photonic source and whose idea we have patented. While considering completely general quantum attacks, we certify randomness at a rate of 1:1 Gbps with a rigorous security parameter of 10-20. Our security proof is entirely composable, thereby allowing the generated randomness to be utilised for arbitrary applications in cryptography and beyond.